Transporters Involved in Root Nitrate Uptake and Sensing by Arabidopsis - Noguero, Mélanie; Lacombe, Benoît (Frontiers in Plant Science, 2016)
Most plants use nitrate (NO3-) as their major nitrogen (N) source. The NO3- uptake capacity of a plant is determined by three interdependent factors that are sensitive to NO3- availability: (i) the functional properties of the transporters in the roots that contribute to the acquisition of NO3- from the external medium, (ii) the density of functional transporters at the plasma membrane of root cells, and (iii) the surface and architecture of the root system. The identification of factors that regulate the NO3--sensing systems is important for both fundamental and applied science, because these factors control the capacity of plants to use the available NO3-, a process known as the “nitrate use efficiency”. The molecular component of the transporters involved in uptake and sensing mechanism in Arabidopsis roots are presented and their relative contribution discussed.